A bibliometric analysis of urban sprawl - SİYAVUŞ, AHMET EMRAH (Routledge, 2021)
This study aims to reveal the scientific structure of the “urban sprawl” issue by bibliometric analysis. Urban sprawl has become an actual problem with population growth, population mobility and urbanization in recent years. 575 publications in journals covered by SSCI, SCI-Expanded and A&HCI indexes accessed via the Web of Science database were included in this analysis. Descriptive and bibliometric analysis methods were used to analyze the publications within the scope of the research. The distributions of the publications by years, countries, journals, and authors were examined. Visual maps were created by analyzing coauthor, co-citation, and keyword patterns with the VOSviewer software. The countries, journals, authors that contributed the most to the literature are of western origins, principally the USA. The most co-cited researchers study in the fields such as health, city and regional planning, geography, environmental sciences, economics, remote sensing, and GIS. Hereof, it has been comprehended that the urban sprawl issue has been expanded to a scientific topic by researchers from different fields, especially after the 2000s. This study provides a scientific literature map of the urban sprawling issue and aims to offer scientists ideas for future research problems. © 2021 Applied Geography Conferences.
Keywords: bibliometric analysis; co-citation analysis; co-word analysis; coauthor analysis; Urban sprawl